Piracetam potentiates neuronal and behavioral effects of ketamine - Igor I. Abramets; Yuriy V. Kuznetsov; Dmitriy V. Evdokimov; Tamara O. Zaika (Belgorod National Research University, 2019)
Introduction: Ketamine has a fast, but short-term antidepressant effect. To support the therapeutic effect, repeated administrations of the drug are needed, which causes cognitive disorders. The drugs with cerebroprotective action can potentially intensify the main and weaken the side effects of drugs. Materials and methods: The impact of ketamine (5 and 20 μM), piracetam (100 μM), and their combinations on the synaptic transmission was studied on hippocampal slices in the CA1 area of rat hippocampus by means of electrophysiological methods. In behavioral experiments were aimed at studying an impact of the used drugs on the predictors which mark depressant behavior of rats: the duration of immobilization in a forced swimming test and preference for the consumption of sucrose solution (comparably with water). The behavioral experiments were performed on intact rats and rats with behavioral depression induced by chronic swimming stress. Results and discussion: Ketamine (5 and 20 μM) potentiates synaptic transmission in the radial layer of the CA1 hippocampal area. At a smaller concentration, ketamine potentiates synaptic transmission only due to the postsynaptic action, and at a greater concentration - with help of post- and presynaptic action. Piracetam (100 µM), like ketamine at a concentration of 5 μM stimulated synaptic transmission, but to a lesser degree. Ketamine at a concentration 5 μM under combined effect with piracetam induced the same effect as that at a concentration of 20 μM without piracetam, only due to a postsynaptic action. Ketamine at doses of 5 and 20 mg/kg one hour after a single systemic administration resulted in the reduced immobilization duration, but not predictors of preference for consuming a sweet solution; piracetam at a dose of 100 mg/kg under these conditions had no impact on the parameters of the rats' behavior. The studied behavior parameters in cases of behavioral depression also changed after a single administration of ketamine at the doses of 5 and 20 mg/kg. Piracetam significantly stimulated an antidepressant action of ketamine under these circumstances. Conclusion: Piracetam potentiates a ketamine-induced enhancement of the synaptic transmission at the radial layer of the CA1 hippocampal area when investigating at the brain slices. Piracetam stimulates an antidepressant action of a single dose of ketamine in cases of behavioral depression, though it has no antidepressant effect when administered at a single dose.